2021
DOI: 10.1097/pgp.0000000000000735
|View full text |Cite
|
Sign up to set email alerts
|

The Silva Pattern-based Classification for HPV-associated Invasive Endocervical Adenocarcinoma and the Distinction Between In Situ and Invasive Adenocarcinoma: Relevant Issues and Recommendations From the International Society of Gynecological Pathologists

Abstract: The Silva pattern-based classification for human papilloma virus–associated invasive adenocarcinoma has emerged as a reliable system to predict risk of lymph node metastasis and recurrences. Although not a part of any staging system yet, it has been incorporated in synoptic reports as established by the College of American Pathologists (CAP) and the International Collaboration on Cancer Reporting (ICCR). Moreover, the current National Comprehensive Cancer Network (NCCN) guidelines include this classification a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
27
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 52 publications
0
27
1
Order By: Relevance
“…This has important implications regarding the differential diagnosis and management of CCC since the application of the Silva pattern classification system to HPVI ECA is currently not recommended by the International Society of Gynecologic Pathologists (ISGyP). 15 The prognosis of cervical CCC is stage-dependent, yet the inherent risk associated with this histology is not well established. While recent work has demonstrated that HPVI ECA have a worse prognosis than HPVA ECA, no study has looked specifically at a large cohort of CCC as compared with GTA.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This has important implications regarding the differential diagnosis and management of CCC since the application of the Silva pattern classification system to HPVI ECA is currently not recommended by the International Society of Gynecologic Pathologists (ISGyP). 15 The prognosis of cervical CCC is stage-dependent, yet the inherent risk associated with this histology is not well established. While recent work has demonstrated that HPVI ECA have a worse prognosis than HPVA ECA, no study has looked specifically at a large cohort of CCC as compared with GTA.…”
mentioning
confidence: 99%
“…In addition, we have observed Silva patterns A and B in cervical CCCs, particularly in small, early-stage tumors, as well as exophytic lesions. This has important implications regarding the differential diagnosis and management of CCC since the application of the Silva pattern classification system to HPVI ECA is currently not recommended by the International Society of Gynecologic Pathologists (ISGyP) 15…”
mentioning
confidence: 99%
“…Non-HPV-related cervical cancer is rare, representing <1% of newly diagnosed cases, with histologies including cervical neuroendocrine, small cell, and large cell carcinomas ( 30 ). In comparison of the two major histologies, SCCdevelops from the ectocervix's squamous epithelia and AC develops from the endocervix'sglandular epithelia ( 29 ) Studies suggest that the incidence of AC appears to be increasing in some countries while SCC incidence is decreasing ( 29 , 47 ). The rise is seen among young women, partly due to cohort effect and partly due to cytology screening, which is less effective for detection of AC compared to SCC ( 29 ).…”
Section: Hpv Attributes Screening Diagnosis Treatment and Preventionmentioning
confidence: 99%
“…The rise is seen among young women, partly due to cohort effect and partly due to cytology screening, which is less effective for detection of AC compared to SCC ( 29 ). Although there is growing evidence that ACs have different epidemiology, prognostic variables, patterns of dissemination, and treatment failure following therapy compared to SCCs, both are staged and treated similarly ( 47 ). Silvaclassification, which stratifies invasion in three patterns, is used to determine HPV-related CAC ( 47 , 48 ).…”
Section: Hpv Attributes Screening Diagnosis Treatment and Preventionmentioning
confidence: 99%
See 1 more Smart Citation